[OP.5A.04] A URINARY FRAGMENT OF MUCIN 1 SUBUNIT ALPHA IS A NOVEL BIOMARKER PREDICTING RENAL DYSFUNCTION IN THE GENERAL POPULATION. (September 2017) - Zhang, Z.; Ravassa, S.; Pejchinovski, M.; Yang, W.; Zürbig, P.; López, B.; Wei, F.F.; Thijs, L.; Jacobs, L.; González, A.; Voigt, J.; Verhamme, P.; et al.
Abstract : Objective: Chronic kidney disease (CKD) is a major health problem affecting the quality of life of millions of people. Renal interstitial fibrosis is a universal predictor of the decline in renal function and is characterized by exaggerated deposition of extracellular matrix (ECM) by an expanding population of fibroblasts and myofibroblasts. Our objective was to gain insight in the pathophysiological pathways leading to renal injury by sequencing urinary peptides and thereby identifying the parent proteins from which they are derived. In a representative population sample, we investigated the associations of eGFR with sequenced urinary fragments markers. Design and method: In 805 randomly recruited Flemish (50.8% women; mean age, 51.1 years), we estimated glomerular filtration rate (eGFR) by the CKD-EPI method. We staged CKD according to the KDOQI guideline. We analysed 74 sequenced urinary peptides with signal amplitude different from undetectable in > 95% of participants. Follow-up measurements of eGFR and CKD stage were available in 597 participants. Results: In multivariable analyses, baseline eGFR decreased (P <  = 0.022) with urinary fragments of mucin 1 (standardized association size expressed in mL/min/1.73 m 2, −4.48), collagen III (−2.84) and fibrinogen (−1.70) and was bi-directionally associated (P <  = 0.0006) with two urinary collagen I fragments (+2.28 and −3.20). eGFR changes over 5 years (follow-up minus baseline) resulted in consistent estimates (P <  = 0.025) for mucin 1 (−1.85), collagen (−1.37 to 1.43) and fibrinogen (−1.45) fragments. Relative risk of having or progressing to CKD stage > = 3 was associated with mucin 1. Partial least square analysis confirmed mucin 1 as the strongest urinary marker associated with decreased eGFR with a score of 2.47 compared with 1.80 for a collagen I fragment as next contender. Mucin 1 predicted progression to CKD stage > = 3 over and beyond microalbuminuria (P = 0.011). Conclusions: In the general population, shedding of the mucin 1 subunit α, an extracellular protein expressed in renal tubular epithelium, is the strongest correlate and predictor of renal impairment and outperforms microalbuminuria. Mucin 1 might be a new target for screening, prevention and treatment of CKD.